Replantation of Anterior Avulsed Teeth: A Case Report - Hadriyanto, Wignyo; Widyastuti, Andina; Wardani, Lukita; Nari Ratih, Diatri; Bernadeti Sri Widayanto, Prisca; Surya, Antonius (KnE Medicine, 2022)
Background: Tooth avulsion is described as a displacement of the tooth from its socket. Replantation on an avulsion permanent dentition is a condition that needs immediate treatment. Replantation of the avulsed tooth can be done in a span of less than 12 hr. Avulsion of tooth may occur due to trauma. Factors that determine healing after replantation are media storage, periodontal tissue damage, extra-alveolar period and intact alveolar socket. The main goal of the replantation is to maintain and treat the periodontal tissue and alveolar contour, and thus retain the dentition for esthetic condition. Objective: To find out the effectiveness of replantation for preserving avulsion of tooth. Case Report: A 42-year-old woman was referred to Universitas Gadjah Mada Dental Hospital with avulsed secondary mandibular incisor (32) after a motorcycle accident that had taken place the night before. The patient was traumatized for more than 12 hr. Based on the clinical examination, tooth 32 was avulsed. Radiographic examination showed no bone fracture. Root canal treatment was performed, and then replantation was carried out, followed by splinting using archbar. Three months after replantation, clinical and radiographic examinations were performed. Results: All mandibular incisors were in good condition. The patient showed good result, and even the replantation was done by exceeding the golden period time. The patient was instructed to maintain her oral hygiene. Conclusion: Immediate treatment of avulsion tooth and the right procedure can affect the success of the treatment. From this viewpoint, replantation is one of the appropriate treatments for preserving avulsion of tooth. Keywords: avulsed tooth, replantation, splinting